DETERMINAN FIRM VALUE DALAM KELOMPOK MARKET-BASED FIRM SIZE YANG BERBEDA - Priyatna, Gustiara Kusuma; Vestari, Mekani (Jurnal Akuntansi dan Pajak, 2024)
Large fluctuations in firm value will make it difficult for investors to make investment decisions, especially those related to long-term investments. Thus, research related to the determinants of firm value is still relevant. However, in previous studies there were still inconsistencies in the results. Several other studies have shown that there are differences in investor responses to different market-based firm size. Therefore this study aims to, first, get empirical evidence of the effect of enterprise risk management, profitability, leverage, liquidity, capital expenditure, sales growth, and firm size on firm value. Second, to get empirical evidence of differences in the effect of company fundamentals on firm value between groups of companies with high market capitalization and low market capitalization. The sample in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2014–2018. The sample was selected by using purposive sampling method. The analysis tool used is multiple linear regression. The results showed that enterprise risk management, profitability, and sales growth have an effect on firm value in both high and low market capitalization samples, the influence of company fundamentals on firm value in the high market capitalization group is greater than the low one. The contribution of this study supports the difference of the firm's fundamental effect on firm value in different market-based firm size. Keywords : firm value, enterprise risk management, profitability, sales growth